Catalystic wet oxidation of wastewater containing acrylic acid - Keong, Lau Weng (2013)
Acrylic acid (AA) is one of the hazardous organic compounds that can be found in industrial wastewater which can cause serious damage to the environment and health. From this research, catalytic wet air oxidation (CWO) process has been used with the presence of Manganese-Cerium Oxide catalyst in order to oxidise acrylic acid in the less severe operating condition. In the present research, the Manganese-Cerium Oxide catalyst (Ce-Mn-1) was prepared by co-precipitation and characterized by using X- ray diffraction (XRD), X-ray flusoncen (XRF), Brunauer, Emmett, and Teller theory (BET) and Barrett, Joyner, and Halenda (BJH) analysis. In addition, performance of the catalyst in CWO of wastewater containing Acrylic Acid was obtained by manipulating different operating parameters, which are temperature, and the concentration of Acrylic Acid. The catalytic activity was analyzed by Chemical Oxygen Demand (COD) analysis method. The catalyst with manganese/cerium ratio 67/33 was successful synthesized with specific surface area, 83.1155 m2g-1 and pore volume 0.3031cm3g-1. Although the synthesized catalyst showed good physical characteristic but the literature COD reduction data obtained is fluctuating due to the side reaction polymerization and formation of carbonic acid during the experiments. As the conclusion the characteristics of catalyst shown a good result but due to the side reaction occur during the experiments, the catalytic activity can’t be determined.